2001
DOI: 10.1111/j.1752-0606.2001.tb01152.x
|View full text |Cite
|
Sign up to set email alerts
|

Attachment Injuries in Couple Relationships: A New Perspective on Impasses in Couples Therapy

Abstract: This article identifies and operationalizes the newly defined construct of attachment injury. An attachment injury occurs when one partner violates the expectation that the other will offer comfort and caring in times of danger or distress. This incident becomes a clinically recurring theme and creates an impasse that blocks relationship repair in couples therapy. An attachment injury is characterized by an abandonment or by a betrayal of trust during a critical moment of need. The injurious incident defines t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
174
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(200 citation statements)
references
References 21 publications
7
174
0
3
Order By: Relevance
“…First, because stress has been shown to activate representations concerning romantic attachment (e.g. Mikulincer and Orbach, 1995), and second, because in situations of distress the couple relationship may be more vulnerable to attachment injuries (Johnson et al, 2001). Johnson and colleagues (2001) have defined an attachment injury as a negative attachment-related event in which one partner is inaccessible and unresponsive in times when the other partner has an urgent need for his or her caring and support; for example, when having a miscarriage or when receiving the diagnosis of infertility.…”
Section: Discussionmentioning
confidence: 99%
“…First, because stress has been shown to activate representations concerning romantic attachment (e.g. Mikulincer and Orbach, 1995), and second, because in situations of distress the couple relationship may be more vulnerable to attachment injuries (Johnson et al, 2001). Johnson and colleagues (2001) have defined an attachment injury as a negative attachment-related event in which one partner is inaccessible and unresponsive in times when the other partner has an urgent need for his or her caring and support; for example, when having a miscarriage or when receiving the diagnosis of infertility.…”
Section: Discussionmentioning
confidence: 99%
“…The largely understudied HPA axis hormone DHEA is fundamental to development and offers the opportunity to deepen our knowledge regarding the key attachment behavior of confiding, which is considered analogous to the trademark of the infant attachment system that is proximity-seeking (Bifulco et al, 2002;Freeman & Brown, 2001;Johnson et al, 2001). In the current study, we found that the hormones cortisol and DHEA are differentially associated with dimensions of attachment in female adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Developing autonomy from parents, or individuating, is a fundamental psychosocial task of adolescence identified by developmental theorists (for example Erikson, 1968). From adolescence forward, one dimension of attachment behavior suggested to be especially important is the ability to disclose and confide in a clear direct way about attachment needs and fears (Johnson, Makinen, & Millikin, 2001). Confiding in a close other is the analogue of the hallmark attachment behavior of seeking proximity to a caregiver in childhood and using caregivers as a safe haven to regulate feelings of insecurity and distress (Bifulco, Moran, Ball, & Bernazzani, 2002;Freeman & Brown, 2001;Johnson et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, individuals with victimiza tion histories grew up to be less comfortable with intimacy and trusting others, more likely to fear abandonment, and more likely to suffer from a low self esteem. Thus, it seems reasonable to hypothesize that negative relationship events (e.g., victimization, rejection, or betrayal) would be linked to more negative or insecure views of close relationships (Johnson et al, 2001). …”
Section: Maladaptive Peer and Romantic Experiencesmentioning
confidence: 99%